ASSESSMENT OF SAFETY LEVELS IN OPERATION ROOMS AT TWO MAJOR TERTIARY CARE PUBLIC HOSPITALS OF KARACHI. SAFE SURGERY SAVES LIFE - Minhas, Muhammad Saeed; Muzzammil, Muhammad; Effendi, Jahanzeb (Journal of Ayub Medical College Abbottabad, 2017)
Background: The objectives of this study are to determine the knowledge and attitude towards surgical safety among the health care professionals including surgeons, anaesthetist, hospital administrators, and operation room personnel and raise awareness towards the importance of safe surgery. Method: A pilot cross- sectional study of 543 healthcare providers working in the operating rooms and the surgical intensive care units was conducted in two tertiary care hospitals, within a study period of one month. A structured questionnaire was constructed and an informed verbal consent was taken. The questionnaire was then distributed; data collected and analysed on SPSS 20.0. Results: A total of 543 respondents participated in the study out of which there were 375 (69%) men and 168 (31%) women. The ages ranged between 23-58 years, mean 40.5±24.74. There were110 (20.25%) surgeons, 58 (10.68%) anaesthetist, 132 (24.30%) trainees, 125 (23.02%) technicians, and were 118 (21.73%) nurses. The question regarding briefing operation room personnel is important for patient safety was agreed by 532 (98%) respondents. Amongst the respondents, 239 (44%) did not feel safe to be operated in their own setup. Team communication improvement through the check list implementation was agreed by 483 (89%) respondents. 514 (94.7%) opted for the checklist to be used while they are being operated. That operation room personnel frequently disregard established protocols was agreed by 374 (69%) respondents. 193 (35.54%) of the respondents stated that it is difficult for them to speak up in the or if they perceive a problem with patient care. Conclusion: Operation room personnel were not aware of several important areas related to briefing, communication, safety attitude, following standard protocols and use of WHO Surgical Safety check list. A pre-post intervention study should be conducted after formal introduction of the Checklist. Successful implementation will require taking all stake holders on board and rigorous training workshops, reinforcing and revisiting. Keywords: Knowledge, Patient Safety, Operating rooms, Patient Care, Checklist, Critical Care